2017
DOI: 10.1007/s10661-017-6400-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coal spoil amendment on heavy metal accumulation and physiological aspects of ryegrass (Lolium perenne L.) growing in copper mine tailings

Abstract: Copper mine tailings pose many threats to the surrounding environment and human health, and thus, their remediation is fundamental. Coal spoil is the waste by-product of coal mining and characterized by low levels of metals, high content of organic matter, and many essential microelements. This study was designed to evaluate the role of coal spoil on heavy uptake and physiological responses of Lolium perenne L. grown in copper mine tailings amended with coal spoil at rates of 0, 0.5, 1, 5, 10, and 20%. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Correspondingly, these contents were enhanced by 1.2 and 3.5 times in the farmland soil as compared to the control. The enhancement of chlorophyll and carotenoid contents could be attributed to the lowered loss of essential macroÀ and microelements supplied with the pigment biosynthesis as well as immobilization of availability of PTEs (Chu et al, 2018) after biodegradable chelator washing. Ye et al (2016) showed that the chlorophyll contents of L. sativa increased by 47% after cultivation in a soil that was washed twice, in comparison with plants cultivated in the original contaminated soil.…”
Section: Removal Efficiencies and Plant-availability Of Metalsmentioning
confidence: 99%
“…Correspondingly, these contents were enhanced by 1.2 and 3.5 times in the farmland soil as compared to the control. The enhancement of chlorophyll and carotenoid contents could be attributed to the lowered loss of essential macroÀ and microelements supplied with the pigment biosynthesis as well as immobilization of availability of PTEs (Chu et al, 2018) after biodegradable chelator washing. Ye et al (2016) showed that the chlorophyll contents of L. sativa increased by 47% after cultivation in a soil that was washed twice, in comparison with plants cultivated in the original contaminated soil.…”
Section: Removal Efficiencies and Plant-availability Of Metalsmentioning
confidence: 99%